2022
DOI: 10.1083/jcb.202203021
|View full text |Cite
|
Sign up to set email alerts
|

Endomembranes promote chromosome missegregation by ensheathing misaligned chromosomes

Abstract: Errors in mitosis that cause chromosome missegregation lead to aneuploidy and micronucleus formation, which are associated with cancer. Accurate segregation requires the alignment of all chromosomes by the mitotic spindle at the metaphase plate, and any misalignment must be corrected before anaphase is triggered. The spindle is situated in a membrane-free “exclusion zone”; beyond this zone, endomembranes (mainly endoplasmic reticulum) are densely packed. We investigated what happens to misaligned chromosomes l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…These findings imply that only a low number of unattached polar chromosomes could induce moderate mitotic delays, which would lead to mis-segregation of unaligned chromosomes. Accordingly, studies that used CENP-E perturbations reported mis-segregation of one or a few unaligned polar chromosomes after moderate mitotic delays in HeLa [103], RPE1 [188,189], and mouse embryonic cells [190]. A similar phenomenon was observed after treatment of cells with nanomolar doses of nocodazole [186].…”
Section: Different Ways To Mis-segregation Through Polar Chromosomesmentioning
confidence: 77%
See 2 more Smart Citations
“…These findings imply that only a low number of unattached polar chromosomes could induce moderate mitotic delays, which would lead to mis-segregation of unaligned chromosomes. Accordingly, studies that used CENP-E perturbations reported mis-segregation of one or a few unaligned polar chromosomes after moderate mitotic delays in HeLa [103], RPE1 [188,189], and mouse embryonic cells [190]. A similar phenomenon was observed after treatment of cells with nanomolar doses of nocodazole [186].…”
Section: Different Ways To Mis-segregation Through Polar Chromosomesmentioning
confidence: 77%
“…Interestingly, the SAC response was robust since Mad1 was recruited on unaligned kinetochores in such cells, and mitotic delays were at the level of a few hours. Moreover, anaphase onset was not the result of 'cohesion fatigue' or 'mitotic slippage' [191,192] since it was preceded by the loss of Mad proteins from unaligned kinetochores, implying that both sister kinetochores acquired endon connections that were able to satisfy the SAC [103,186,188,189]. However, it is unclear what types of attachment could satisfy the SAC at the pole since syntelic, monotelic, and lateral attachments induce a large SAC response [134], although it is possible that the SAC signal wears faster over time if stable end-on attachments are present at one of the sister kinetochores [125,193].…”
Section: Different Ways To Mis-segregation Through Polar Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…When ER membrane biogenesis is increased by enhanced fatty acid synthesis, this leads to higher viscosity of the cytoplasm and ultimately to chromosome mis-segregation ( Merta et al, 2021 ). Moreover, chromosomes that become unsheathed by the ER are more prone to segregation errors ( Ferrandiz et al, 2022 ). Hence, ER reorganization may be a passive event, required for faithful mitosis and even distribution of this organelle to daughter cells ( Smyth et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…To study this, Ferrandiz et al ( 5 ) artificially induced chromosome misalignment through inhibiting centromere-associated protein E (CENP-E), a kinesin-like motor protein that is essential for correct chromosome alignment ( 6 ). In addition, they used a system in which the Y chromosome can be forced to detach from the spindle, resulting in misalignment.…”
mentioning
confidence: 99%